Level of Knowledge Coastal People on Earthquake and Tsunami Disasters Mitigation in Bengkulu, Indonesia (Asian Journal of Applied Sciences, 2017)
The classic problem in disaster mitigation activities is in planning, implementation, and sustainability. One of the contributing factors is the unavailability of information locally about the model of natural disaster occurrence and the model of human behavior as an object that is directly affected by the incident. We have conducted field surveys as well as distributing questionnaires in some coastal areas in the Province of Bengkulu. The data obtained are presented in the form of zoning maps and mathematical models that can illustrate the human behavior of earthquake and tsunami disaster mitigation. The kriging interpolation method is used in zoning map of coastal community knowledge level about earthquake and tsunami disaster mitigation. While the Structural Equation Modelling is used to see the relationship between mitigation variables with earthquake and tsunami disaster risk variables. Conclusions from the results of the study, based on simultaneous measurements of the five disaster mitigation variables, most of the coastal areas located in Mukomuko, Bengkulu Tengah and Seluma districts are included in areas with poorly prepared zone criteria. Partially, especially for Policy Statement variables, almost all districts in Bengkulu Province are perceived not yet ready by respondents from this research. Based on the resulting structural equation model, the reduction of the earthquake and tsunami risk impacts is strongly influenced by emergency response plans and disaster warning system factors.